Periodical room. - Unknown:::Creator::::::::::::
Written on verso: "Florence Keegan; Wasn't your first office here, Joyce? The near end was a storage--workroom when I was new. I remember: when Helen (the next part of the sentence is upside down, located at the top) came to apply for her first job we met there." Periodical Room 1941."